Cause of Ascending Aortic Dilatation in Patients with Bicuspid Aortic Valves: The Final Link - Robicsek, Francis; Madjarov, Jeko M.; Padera, Robert F., Jr. (The Thoracic and Cardiovascular Surgeon, 2020)
Background This article discusses about the cause of dilatation of the ascending aorta in patients with congenitally bicuspid aortic valves (CBAVs). Some members of the profession believe that it is genetic, while others attribute it to turbulence. The author previously presented in vitro data proving that CBAVs are inherently morphological stenotic, even in the absence of measurable gradient and clinical symptoms. This article reinforces the view that the dilatation of the ascending aorta in patients with CBAV represents a “poststenotic dilatation” by demonstrating that the structure of the aortic wall is normal in infants who have CBAV as a sole cardiac anomaly.Methods The aortic wall was studied in newborns who had CBAV as the sole cardiovascular anomaly and in those where CABV was associated with other inborn cardiovascular defects.Results We found that in patients where CBAV is the sole cardiovascular anomaly, aortic structure is normal at birth, but abnormal if additional cardiovascular anomalies are present.Conclusions Dilatation of the ascending aorta in patients, where CBAV is the only cardiovascular anomaly, is caused by turbulence (poststenotic dilatation). If additional cardiovascular anomalies are present, this process may be exaggerated by genetic abnormalities of the aortic wall.
Keywords: aortic dilatation; bicuspid aortic valves